2011
DOI: 10.1111/j.1468-1331.2010.03321.x
|View full text |Cite
|
Sign up to set email alerts
|

Severity of dystonia is correlated with putaminal gray matter changes in Myoclonus-Dystonia

Abstract: This study provides further evidence for the involvement of putamina as important motor structures in the pathophysiology of (myoclonus-) dystonia. Changes in these structures are associated with the severity of dystonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Some studies associated FHD with anatomical abnormalities at the cortical level (Garraux et al, 2004; Delmaire et al, 2007), some others to sub-cortical irregularities (Draganski and Bhatia, 2010; Granert et al, 2011b). In particular, part of the evidence from structural brain imaging on the pathophysiology of dystonia highlights the role of aberrations in subcortical structures, including the basal ganglia (Bhatia and Marsden, 1994; Krystkowiak et al, 1998; Draganski et al, 2009; Beukers et al, 2011), mesencephalon (Vidailhet et al, 1999), and the cerebellum–thalamus–cortex axis (Argyelan et al, 2009). Conversely, other studies associated FHD with structural anomalies in the sensory-motor (Garraux et al, 2004; Delmaire et al, 2007) and the premotor cortex (Granert et al, 2011a).…”
Section: Sensory-motor Deficits In Focal Dystoniamentioning
confidence: 99%
“…Some studies associated FHD with anatomical abnormalities at the cortical level (Garraux et al, 2004; Delmaire et al, 2007), some others to sub-cortical irregularities (Draganski and Bhatia, 2010; Granert et al, 2011b). In particular, part of the evidence from structural brain imaging on the pathophysiology of dystonia highlights the role of aberrations in subcortical structures, including the basal ganglia (Bhatia and Marsden, 1994; Krystkowiak et al, 1998; Draganski et al, 2009; Beukers et al, 2011), mesencephalon (Vidailhet et al, 1999), and the cerebellum–thalamus–cortex axis (Argyelan et al, 2009). Conversely, other studies associated FHD with structural anomalies in the sensory-motor (Garraux et al, 2004; Delmaire et al, 2007) and the premotor cortex (Granert et al, 2011a).…”
Section: Sensory-motor Deficits In Focal Dystoniamentioning
confidence: 99%
“…Finally, Beukers et al . [25] demonstrated that the severity of dystonia in MDS patients correlated with increased grey matter volumes in the putamen, highlighting the importance of this structure in MDS.…”
Section: Myoclonus-dystonia Syndrome (Mds; Dyt11)mentioning
confidence: 99%
“…DYT‐ SGCE is the main cause of myoclonus‐dystonia and is the result of a mutation of the epsilon sarcoglican gene ( SGCE ). In DYT‐SGCE, and similarly to other dystonias, structural neuroimaging studies and pallidal neuronal activity recordings suggest a dysfunctional striato‐pallido‐thalamo‐cortical pathway . Interestingly, DBS of the internal globus pallidus (GPi) results in a dramatic and sustained improvement of both myoclonus and dystonia.…”
mentioning
confidence: 99%